DECOLONISING GLOBAL TRADE TARIFFS: INDONESIA’S STRATEGY IN RESPONSE TO THE WTO’S 1.8% PROJECTION FOR 2026 - Gunawan Widjaja; Nofianty Helyo (ADISAM Publisher, 2026)
This article discusses the decolonisation of global trade tariffs as a conceptual and practical strategy for Indonesia in response to the WTO’s projection of a 1.8% slowdown in global trade by 2026. This study highlights that the global tariff system is not entirely neutral, but rather still reflects historical inequalities that favour developed nations and place developing nations in a subordinate position within the international value chain. Using a literature review approach, this article outlines two main focuses: the deconstruction of tariff inequalities in the global economy and Indonesia’s response strategies through export market diversification, industrial downstreaming, domestic market protection, and economic diplomacy. The findings indicate that tariff decolonisation is not merely a normative agenda, but also a strategic instrument for strengthening economic sovereignty, enhancing national competitiveness, and expanding Indonesia’s development policy space amidst global trade uncertainty.